A study on aflatoxin content in dates available in domestic market in India - Ashish Mukherjee; Manvi Sharma; Savita Latkar; Priya Maurya (International Journal of Pharmacy and Analytical Research, 2022)
Phoenix dactylifera, commonly known as date or date palm, is a flowering plant species in the palm family, Arecaceae, cultivated for its edible sweet fruit. Although its place of origin is unknown because of long cultivation, it probably originated from lands around Iraq. Dates have been a staple food of the Middle East and the Indus Valley for thousands of years. The Ancient Egyptians used the fruits to make date wine, and ate them at harvest. Dates make a sweet, nutritional snack and can be eaten as they come, or glazed with syrup. The date fruit consists of 70 % carbohydrates (mostly sugars), making it one of the most nourishing natural foods available to man. In most varieties, the sugar content of a date fruit is almost entirely of the inverted form (namely glucose and fructose), important for persons who cannot tolerate sucrose. The invert sugar in dates is immediately absorbed by the human body without being subjected to the digestion that ordinary sugar undergoes. Dates are of two types Unpitted and pitted. Pitted dates are fruits that had their stones removed. Pitted dates are without the pit are loaded with natural sweetness and can be used for noshing or baking. Unpitted dates is containing the pits or stones. Pitted dates are firm, easy to chop up and can be used in variety of recipes. The dates are directly consumed without any processing. The aflatoxins are a group of chemically similar toxic fungal metabolites (mycotoxins) produced by certain moulds of the genus Aspergillus growing on a number of raw food commodities. Aflatoxins are highly toxic compounds and can cause both acute and chronic toxicity in humans and many other animals. The aflatoxins consist of ab out 20 similar compounds belonging to a group called the difuranocoumarins, but only four are naturally found in foods. These are aflatoxins B1, B2, G1 and G2. Aflatoxin B1 is the most commonly found in food and also the most toxic and classified by the International Agency for Research on Cancer (IARC) as 1 st class carcinogen. The Dates, which is directly being consumed by human being, to be free from Aflatoxin contamination or contain the permissible limit of same. In the present study Aflatoxin B1 contamination have been carried out in two varieties of dates(pitted and unpitted) collected from different parts of India and also to assess whether the fruits were safe for human consumption. The aflaoxin in dates have been analysed using HPTLC. 50 Samples of unpitted dates analyzed for the estimation of Aflatoxin. 49 samples are having Aflatoxin content below detection level. Only one sample contains 4.771 ppb of Aflatoxin. In FSSAI Max limit for Aflatoxin is 30 ppb. 51 Samples of pitted dates analyzed for the estimation of Aflatoxin. All the 51 samples are having Aflatoxin content below detection level.